The Effects of Amino Acids Enriched Del Nido Cardioplegia on Myocardial Leucocyte Accumulation and Ventricular Functions in Patients Undergoing Coronary Artery Bypass Grafting Surgery - Temizturk, Zeki; Azboy, Davut; Uysal, Ayhan (Forum Multimedia Publishing, Llc, 2021)
Background: One of the main sources of ischemia/reperfusion injury (IRI) and release of free oxygen radicals (FORs) during extracorporeal circulation (ECC) during cardiac surgery is neutrophils. In this study, we investigated the potential effects of our modification of del Nido cardioplegia (mDNC) (amino acids enriched del Nido cardioplegia) on myocardial polymorphonuclear leucocyte (PMNL) accumulation. We also compared the effects of our mDND and classical del Nido cardiplegia (cDNC) on ventricular contractile functions in coronary artery bypass grafting (CABG) surgery. Patients and methods: Our study included 100 isolated CABG patients with similar characteristics, including age, gender, preoperative medications, diabetes, hypertension, and left ventricular ejection fraction (LVEF). The patients were divided into two groups. Amino acids supplemented del Nido cardioplegia (L-aspartate and L-glutamate at a dose of 13 milimol/L) in 50 patients (study group, G1). In the remaining 50 patients, we used a classical del Nido cardioplegic solution (cDNC) (control group, G2). Myocardial Tru-Cut biopsy from the right ventricle was taken before the institution of ECC and after weaning from ECC in all patients. Cardiac troponine-I (cTn-I), tumor necrosis factor-alpha (TNF-Alpha), Pro-Brain Natriuretic Peptide (Pro-BNP), and lactate levels were measured pre- and postoperatively. Invasive monitoring was performed to provide the left ventricular functions in both groups in the operating room and noted by a blinded anaesthesiologist. Results: Five patients died post-surgery (5%) (two from SG and three from CG (P = .67), due to low cardiac output syndrome or multiorgan failure. At the postoperative period, cardiac output (CO) and stroke volume index (SVI) was higher in mDNC (mean +/- SDS; 32.1 +/- 7 versus 22.2 +/- 6.9 mL/min/m(2) (P < .001). CI was significantly higher in mDNC after surgery (3.10 +/- 0.76 versus 2.40 +/- 0.30L/min/m(2) (P = .002). Ten patients (20%) in mDNC and 16 patients (32%) in cDNC required inotropic support (P < .001). The postoperative inotropic requirement was less in mDNC (6.1 +/- 1.8 mg/kg versus 9.2 +/- 1.9 mg/kg, P < .004). Blood gas analyses from the coronary sinus showed that myocardial acidosis was more severe in the control group [pH (0.10 +/- 0.09 versus 0.054 +/- 0.001; P = .34)]. Blood lactate levels were significantly high in the control group (1.01 +/- 0.007 mmol/L versus 1.92 +/- 0.35 mmol/L) (P = .22). No difference was found when compared with cardioplegia volume in the mDNC and cDNC groups (mDNC = 990.00 +/- 385 mL in DNC = 960 +/- 240 mL, P = .070). An aortic cross-lamp time in the mDNC and cDNC groups were 88.4 +/- 8.9 min, and 93 +/- 11 min, (P = .76), but cardiopulmonary bypass time was significantly low in mDNC (mDNC = 98.3 +/- 22.5 min, DNC = 126 +/- 19.5 min, P = .0020). TNF-Alpha and Pro-BNP levels in patients received mDNC were significantly low (P = .022). Postoperative cardiac enzyme levels (creatine kinase-MB and high sensitive troponin-I) were significantly low in the mDNC group (P = .0034). Myocardial biopsy results showed that myocardial PMNL accumulation was significantly high in the control group (P = .001). The amount of inotropic agent use was significantly high in the control group (P = .003). After weaning from ECC, the left ventricular stroke work index (LVSWI), cardiac index (CI), and heart rate (HR) were significantly high in the study group (P = .032; P = .002; P = .01). Postoperative blood and blood products requirements were significantly low in the mDNC group (P = .002). At pre-discharge echocardiography, the mDNC group demonstrated significantly higher ventricular ejection fraction (37.9 +/- 4.3% and 29.7 +/- 3.8%, respectively (P = .003). Conclusion: Our study findings show that glutamateaspartate supplemented del Nido cardioplegia significantly decrease myocardial PMNL accumulation with reduced release of biochemical markers, including cardiac troponinI, TNF-alpha, and Pro-Bnp. Our study results demonstrated that amino acids supplementation in del Nido cardioplegia has some advantages in CABG patients, including the decrease of perioperative myocardial infarction and increase significantly the left ventricular functions including ventricular SVI and CI.
Keywords: Depleted Blood Cardioplegia; Reperfusion; Protection; Aspartate; Glutamate; Dysfunction; Warm